On board a raft or boat in the retrovirus sea - Svoboda, Jan (Proceedings of the National Academy of Sciences of the United States of America, 2016)
This article summarizes the essential steps in understanding the chicken Rous sarcoma virus (RSV) genome association with a nonpermissive rodent host cell genome. This insight was made possible by in-depth study of RSV-transformed rat XC cells, which were called virogenic because they indefinitely carry virus genetic information in the absence of any infectious virus production. However, the virus was rescued by association of XC cells with chicken fibroblasts, allowing cell fusion between both partners. This and additional studies led to the interpretation that the RSV genome gets integrated into the host cell genome as a provirus. Study of additional rodent virogenic cell lines provided evidence that the transcript of oncogene v-src can be transmitted to other retroviruses and produce cell transformation by itself. As discussed in the text, two main questions related to nonpermissiveness to retrovirus infection remain to be solved. The first is changes in the retrovirus envelope gene allowing virus entry into a nonpermissive cell. The second is the nature of the permissive cell functions required by the nonpermissive cell to ensure infectious virus production. Both lines of investigation are being pursued.
Keywords: kur domácí; Animals; fúze buněk; Genome, Viral; buněčné linie; Proviruses; Chickens; virová transformace buněk; virus Rousova sarkomu; genové produkty env; virus integration; genom virový; Gene Products, env; proviry; Oncogene Protein pp60(v-src); Cell Line; cell transformation; Cell Transformation, Viral; virus rescue; krysa rodu Rattus; onkogenní protein pp60(v-src); Rous sarcoma virus; nonpermissiveness to virus infection; zvířata; Cell Fusion; Rats